Tourism, Information Communication and Technology, Renewable Energy Consumption, Economic Growth and CO2 Emissions in Indonesia - Yaseen, Atif; Suseno , Priyonggo; Shah, Syed Ghulam Hussain (Fakultas Ekonomi dan Bisnis Islam, UIN Sunan Kalijaga Yogyakarta, 2024)
This study uses annual data from 1995 to 2020 to investigate the Impact of Tourism, Information Communication and Technology, Renewable Energy Consumption, and Economic Growth on CO2 Emissions in Indonesia. The relationship between the variables was investigated using an autoregressive distributed lag (ARDL) approach, which considered both the long and short runs. The unit root tests were used to determine the data's stationarity and the F-statistics bound test validated cointegration between variables. This study found short-run and long-term correlations between CO2 emissions from Indonesia's tourism sector, information communication and technology, usage of renewable energy consumption, and economic growth. In the long run, Indonesia's CO2 emissions rise by 0.034% and 0.079%, and in the short run, by 0.040% and 0.092%, with a 1% increase in ICT and economic growth, respectively. Furthermore, decreases in CO2 emissions of 0.050% and 0.287 over the long run and 0.058% and 0.344% over the short run, respectively, may result from a 1% increase in tourism and renewable energy consumption. The study's findings show that although Indonesia's CO2 emissions are growing due to ICT and economic growth, they are falling due to tourism and the use of renewable energy. Further research could be possible with more economic data and modern econometric techniques. According to these findings, in addition to eco-friendly tourist laws, the ICT sector, and renewable energy sources, authorities in Indonesia should prioritize greater environmentally friendly economic growth to protect the country's natural environment.